2017
DOI: 10.1016/j.prevetmed.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards worm egg counts and targeted selective treatment against equine cyathostomins

Abstract: Gastrointestinal nematodes present a major threat to the health and welfare of equids worldwide. Anthelmintic resistance (AR) is increasingly reported and challenges effective control in horses and ponies in many regions. The use of faecal worm egg counts (FECs) to support targeted treatment (FEC-TT) and targeted selective treatment (FEC-TST) has been promoted as an effective deworming strategy that may prolong the useful life of anthelmintics and reduce the costs associated with parasite control. However, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
4
24
0
1
Order By: Relevance
“…It is therefore necessary to consider in-depth the reasons why people are behaving in a certain way, in order to help them to change their behaviour. We know from surveys of horse owners that they are interested in de-worming (Stratford et al, 2014b), but these surveys also corroborate more general human behaviour studies in confirming that social norms are a more powerful influence than professional advice; horse owners are more likely to do what everyone else on the yard does than what the veterinary surgeon advises them to do (Stratford et al, 2014b;Easton et al, 2016;Rose Vineer et al, 2017). Anthelmintics are available from a variety of outlets and, contrary to guidelines, are often sold without investigation of which diagnostics have been performed and which product is most appropriate.…”
Section: Effecting Change Barriers To Changing Owner Behavioursupporting
confidence: 55%
See 3 more Smart Citations
“…It is therefore necessary to consider in-depth the reasons why people are behaving in a certain way, in order to help them to change their behaviour. We know from surveys of horse owners that they are interested in de-worming (Stratford et al, 2014b), but these surveys also corroborate more general human behaviour studies in confirming that social norms are a more powerful influence than professional advice; horse owners are more likely to do what everyone else on the yard does than what the veterinary surgeon advises them to do (Stratford et al, 2014b;Easton et al, 2016;Rose Vineer et al, 2017). Anthelmintics are available from a variety of outlets and, contrary to guidelines, are often sold without investigation of which diagnostics have been performed and which product is most appropriate.…”
Section: Effecting Change Barriers To Changing Owner Behavioursupporting
confidence: 55%
“…Behaviour studies indicate that it is important to understand the motivation of a study population prior to trying to assist that population to change their behaviour. Thus far, research into horse owners has shown that most owners are aware that AHR is an issue; however, they may not consider that it applies to their horses (Rose Vineer et al, 2017). Most horse owners do not use FEC because they are concerned about AHR or even parasitic disease, but rather are driven to do so by other factors such as effects of parasites on performance or a desire to avoid the use of chemicals (Rose Vineer et al, 2017).…”
Section: Effecting Change Barriers To Changing Owner Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…AR on the other hand was not perceived as a risk, and had no effect whatsoever on the adoption intentions of the dairy farmers. A study of Rose Vineer et al ( 92 ) in UK horse owners obtained similar results, but identified perceived knowledge as an additional driver for adoption intention of diagnostic methods. Moreover, perceived knowledge increased the intention to use diagnostics via attitudes, subjective norms, and perceived control.…”
Section: Farmers' Adoption Of Sustainable Controlmentioning
confidence: 72%